Exploring the association of long noncoding RNA expression profiles with intracranial aneurysms, based on sequencing and related bioinformatics analysis - Yi Sun; Yeying Wen; Qishuang Ruan; Le Yang; Shuna Huang; Xingyan Xu; Yingying Cai; Huangyuan Li; Siying Wu (BMC Medical Genomics, 2020)
Abstract Background The present study aims to investigate the complete long non-coding RNA (lncRNA) and messenger RNA (mRNA) expression profiles in Intracranial aneurysm (IA) patients and controls by RNA sequencing, which reveals the lncRNA with predictive value for IA risk. Methods The comprehensive lncRNA and mRNA expression profiles were detected by RNA-Seq in human IA walls and superficial temporal arteries (STAs), followed by bioinformatics analyses, such as GO analysis, KEGG pathway analysis, and CNC network construction. Subsequently, qRT-PCR was used to profile the expression levels of selected lncRNA (lncRNA ENST000000576153, lncRNA ENST00000607042, lncRNA ENST00000471220, lncRNA ENST00000478738, lncRNA MALAT1, lncRNA ENST00000508090 and lncRNA ENST00000579688) in 30 (small) or 130 (large) peripheral blood leukocytes, respectively. Multivariate logistic regression was utilized to analyze the effects of lncRNA on IA. Receiver operating characteristic (ROC) curve was further drawn to explore the value of lncRNA in predicting IA. Results Totally 900 up-regulated and 293 down-regulated lncRNAs, as well as 1297 up-regulated and 831 down-regulated mRNAs were discovered in sequencing. Enrichment analyses revealed that they were actively involved in immune/inflammatory response and cell adhesion/extracellular matrix. Co-expression analysis and further enrichment analyses showed that five candidate lncRNAs might participate in IA’s inflammatory response. Besides, after controlling other conventional risk factors, multivariate logistic regression analysis disclosed that low expression of lncRNA ENST00000607042, lncRNA ENST00000471220, lncRNA ENST00000478738, lncRNA MALAT1 in peripheral blood leukocytes were independent risk factors for IA. LncRNA ENST00000607042 has superior diagnostic value for IA. Conclusions This study reveals the complete lncRNAs expression profiles in IA. The inflammatory response was closely related to IA. Besides, lncRNA ENST00000607042 might be a novel biomarker for IA risk.